Quantification of total phenolic and total flavonoid compounds in sweet basil (Ocimum basilicum L.) leaves, through the optimization of temperature and concentration of ethanol - Qazizadah, Ahmad Zubair; Nakasha, Jaafar Juju; Sinniah, Uma Rani; Megat Wahab, Puteri Edaroyati (International Society for Southeast Asian Agricultural Sciences, 2023)
Sweet basil (Ocimum basilicum L.) is a valuable pharmaceutical herb that is rich in antioxidants. Despite this, the success in extracting those compounds lies on the technique used during the extraction processes. The current study was aimed to establish a suitable extraction technique through different levels of temperature and concentrations of ethanol. The study was conducted in Post-Harvest Laboratory of Agriculture Faculty in Universiti Putra Malaysia, Malaysia from July 2019 to February 2020. The mature dried leaves of sweet basil were exposed to three different temperatures (40, 60 and 80°C) and combined with three concentrations of aqueous ethanol solutions (60, 75 and 90, v/v). The experiment was carried out in 3 X 3 factorial complete randomized design with four replications and three samples per replicate. The highest extraction yield (11.56) was obtained from the combination of 80°C + 90 aqueous ethanol. Meanwhile, the highest total phenolic content (67.02 mg of GAE/g DE), total flavonoid content (44.70 mg QUE/g DE) and antioxidant activity (66.80 in 100 μg/ml) were obtained from the combination of 80°C + 60 aqueous ethanol. Although the highest extraction yield was obtained from 80°C+90, it is however, this study was focusing on the phenolic and flavonoid compounds. Hence, it is recommended to extract the sweet basil leaves under 80°C with 60 aqueous ethanol.